2011
DOI: 10.1039/c1cc10261c
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in hierarchically structured zeolites: synthesis and material performances

Abstract: Hierarchically structured zeolites (HSZs) have attracted increasing attention in the last few years, thanks to their unique hierarchical porous structures combining micro- and mesoporosity and superior material performances, especially in the bulky molecules-involved catalysis and adsorption applications. In this Feature Article, the recent advances in the HSZs synthetic methodologies and material performances in catalysis are overviewed. Further, some perspectives for the future development of HSZs are discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(89 citation statements)
references
References 82 publications
1
86
0
2
Order By: Relevance
“…However, utilization of powdered zeolites for the industrial applications is often limited because of diffusion and access problems arising from the small zeolites pore size ranging of 0.3-1 nm which is similar to the dimensions of molecules [3,4]. The poor diffusion of relatively large reactant molecules or ions to the active sites present in the zeolite micropores may lead to the underutilization of the available zeolite internal surface area and volume, frequent blocking of the diffusion path and rapid zeolites deactivation [3,5]. The catalysis and uptake activity of zeolite is related to both the length of diffusion path and the diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…However, utilization of powdered zeolites for the industrial applications is often limited because of diffusion and access problems arising from the small zeolites pore size ranging of 0.3-1 nm which is similar to the dimensions of molecules [3,4]. The poor diffusion of relatively large reactant molecules or ions to the active sites present in the zeolite micropores may lead to the underutilization of the available zeolite internal surface area and volume, frequent blocking of the diffusion path and rapid zeolites deactivation [3,5]. The catalysis and uptake activity of zeolite is related to both the length of diffusion path and the diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…3 and 4) is probably an artefact. It was outlined by Groen et al [25,26] that a peak with mean pore radius at around 10 Å , observed in pore radius distributions of ZSM-5 obtained from nitrogen isotherms by the BJH method [19], is caused by phase transition (solidification) of the nitrogen adsorbed in the ZSM-5 micropores and not by the presence of real mesopores. Fig.…”
Section: Zeolitization Of Preformed Mesoporous Materialsmentioning
confidence: 99%
“…In recent years, there has been a rapid development in synthesis and applications of hierarchical zeolitic materials. Many excellent reviews highlighting various aspects of the latest progress in this field have been published [6,[8][9][10]13,14,[16][17][18][19][20][21][22][23][24][25][26][27][28][29]. It should be noted that most of them have focused on hierarchical zeolites (HZs).…”
Section: Direct-synthesis Using Zeolite Precursorsmentioning
confidence: 99%
“…Furthermore, some works have also noted that these materials improve the performance of heterogeneous catalysts when used as supports instead of classical zeolites in hydrodesulfuration reactions [328].…”
Section: Synthesis and Structurementioning
confidence: 99%